Employee Performance Based On Compensation, Discipline, and Competency in the Regional Secretariat of Kupang City - Marnisah, Luis; Manafe, Graendy Zimrat; Riwu Kore, Jefirstson R; Alie, Juhaini (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: The performance of government employees called ASN in Indonesia is still considered low by various surveys and data. Factors that are considered to be the phenomenon causing low ASN performance are compensation, discipline, and competence. This study aims to analyze and prove the effect of compensation, discipline, and competence on employee performance. Methodology: The research design used is quantitative research. The population of the study was all employees of the General Section of the Kupang City Regional Secretariat totaling 114 employees. All employees were the research sample with a saturated sampling technique. Data were obtained through questionnaire interviews (Likert scale), observation, and documentation. The research data consisted of primary and secondary data. The data analysis method was multiple linear regression analysis. Results: The results of the study showed a t-value of compensation of 3.283 > t-table of 1.98137. Discipline has a t-value of 5.036 > t-table of 1.98137. The t-value of competency is 2.772 > t-table of 1.98137, and the F-value of 13.263 > F-table of 2.70, which indicates that compensation, discipline, and competency have a positive and significant effect on employee performance in the Regional Secretariat of Kupang City both partially and simultaneously. The three exogenous variables have a "strong" correlation to performance with an R2 value of 97.9%. Findings: This study highlights the importance of adequate employee compensation, high employee discipline as a professional commitment, and high employee competence to achieve high employee performance. Novelty: This study elaborates on the interaction between compensation, discipline, and competence in the context of employee performance in government organizations. Originality: This study contributes to the literature on employee performance at the Kupang City Regional Secretariat by addressing the gap in understanding these variables. Conclusion: Practical thinking is a recommendation for the Regional Secretariat organization to develop strategies to improve employee performance in accordance with the organization's expectations and goals. Type of Paper: Quantitative empirical research paper.